Lasting improvements in manufacturing performance: In search of a new theory - Ferdows, Kasra; De Meyer, Arnoud (Journal of Operations Management, 1990)
AbstractIs there a way to avoid trading off one capability for another in manufacturing? The prevailing wisdom says no. But some manufacturers seem to have been able to defy that: compared to their competitors, they have better quality, are more dependable, respond faster to changing market conditions and in spite of all that, achieve lower costs. How can this be explained?Our aim here is to provide an explanation. We contend that the nature of the trade‐offs among manufacturing capabilities is more complex than has been assumed. Depending on the approach taken for developing each capability, the nature of the trade‐offs change. In certain cases not only can trade‐offs be avoided altogether, but in fact one capability would enhance another. They become cumulative. Moreover, when a capability is developed in this way, it is likely to be more lasting and less fragile than if it were developed at the expense of other capabilities.We go on to suggest a model which shows how this can be done: To build cumulative and lasting manufacturing capability, management attention and resources should go first toward enhancing quality, then—while the efforts to enhance quality are further expanded—attention should be paid to improve also the dependability of the production system, then—and again while efforts on the previous two are further enhanced—production flexibility (or reaction speed) should also be improved, and finally, while all these efforts are further enlarged, direct attention can be paid to cost efficiency. We use data from 1988 European Manufacturing Futures Survey (167 respondents) to test and illustrate our model.While we cannot “prove” our model, nevertheless, we believe there is enough evidence for a critical reexamination of traditional managerial approaches for improving manufacturing performance. For example, except for the cases when there are obvious slacks in the production system, the belief that costs can come down quickly and lastingly needs to be questioned. Lasting cost efficiency in production can be achieved only through improvements in other capabilities.